2004
DOI: 10.1111/j.1600-0609.2004.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in combination with vincristine, epirubicin and dexamethasone (VED) for previously untreated patients with multiple myeloma

Abstract: The present study aimed to evaluate the side-effects and efficacy of thalidomide in combination with an anthracycline-containing chemotherapy regimen in previously untreated myeloma patients. Thalidomide (400 mg/d) was combined with bolus injections of vincristine and epirubicin and oral dexamethasone (VED). Chemotherapy cycles were repeated every 3 wk until no further reduction in myeloma protein was observed, whereas the treatment with thalidomide was continued until disease progression. Thirty-one patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…on May 9, 2018. by guest www.bloodjournal.org From lowest rates reported by other studies, [10][11][12][13]18 it needs to be reduced. Even though the best DVT prophylaxis in patients receiving thalidomide-based regimens has not been established so far, retrospectively, we believe that fixed-dose warfarin might have been inadequate as DVT prophylaxis in our protocol.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…on May 9, 2018. by guest www.bloodjournal.org From lowest rates reported by other studies, [10][11][12][13]18 it needs to be reduced. Even though the best DVT prophylaxis in patients receiving thalidomide-based regimens has not been established so far, retrospectively, we believe that fixed-dose warfarin might have been inadequate as DVT prophylaxis in our protocol.…”
Section: Discussionmentioning
confidence: 90%
“…8 Better results can be obtained when chemotherapeutic agents are added to or administered before 18 the thalidomide-dexamethasone combination. [10][11][12][13] At present, it remains unclear which single or other chemotherapy regimen is the best one to be combined with thalidomidedexamethasone to achieve a higher CR rate associated with an acceptable toxicity. Moreover, it is unknown whether the best quality of response obtained with these combinations does affect survival parameters of patients with MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] After the approval of thalidomide for the treatment of MM, 2 further treatment options have appeared. A thalidomide analog known as lenalidomide, which is effective in vitro at lower concentrations than thalidomide and is potentially less toxic, was developed.…”
Section: Org Frommentioning
confidence: 99%
“…As shown in Table 2, in phase II studies evaluating thalidomide plus anthracycline-containing chemotherapy regimens without thromboprophylaxis, incidences of 10% to 58% have been reported. 5,[33][34][35] The study with the highest reported incidence of TEE was a large phase II trial evaluating DVd-T in both RRMM and NDMM patients in which 58% of patients developed TEE prior to amendment of the protocol mandating low-dose aspirin thromboprophylaxis. As will be discussed in more detail below, the addition of ASA reduced the incidence of TEE by approximately two-thirds.…”
Section: Thalidomide Plus Cytotoxic Chemotherapymentioning
confidence: 99%